1996
DOI: 10.1122/1.550755
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐mode approach to finite, three‐dimensional, nonlinear viscoelastic behavior of polymer glasses

Abstract: SynopsisIn this study a phenomenological constitutive model is proposed to describe the finite, nonlinear, viscoelastic behavior of glassy polymers up to the yield point. It is assumed that the deformation behavior of a glassy polymer up to the yield point is completely determined by the linear relaxation time spectrum and that the nonlinear effect of stress is to alter the intrinsic time scale of the material. A quantitative three-dimensional constitutive equation for polycarbonate as a model polymer was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
134
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(135 citation statements)
references
References 18 publications
1
134
0
Order By: Relevance
“…It is most often assumed that mechanical stress lowers the activation barriers to molecular mobility, thereby allowing the solid to yield and flow. This simple idea, first proposed by Eyring in 1936 [1], remains the central tenet of several models of plasticity in amorphous solids [2,3]. Other control variables have also been proposed to explain the increased molecular mobility under deformation.…”
Section: Introductionmentioning
confidence: 99%
“…It is most often assumed that mechanical stress lowers the activation barriers to molecular mobility, thereby allowing the solid to yield and flow. This simple idea, first proposed by Eyring in 1936 [1], remains the central tenet of several models of plasticity in amorphous solids [2,3]. Other control variables have also been proposed to explain the increased molecular mobility under deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is to use a so-called multimode approach to describe the complete pre-yield viscoelastic behaviour. In previous work we showed that the behaviour can be accurately captured by a parallel arrangement of eighteen modes [15]. Unfortunately, this solution increases tremendously the computation time and will therefore not be used.…”
Section: Indentation Modellingmentioning
confidence: 99%
“…In the last 20 years, considerable effort has been made to model the post yield behaviour of glassy polymers and a number of 3D numerical models were developed and validated, by Boyce et al at MIT [9][10][11], Paul Buckley et al in Oxford [12][13][14] and our own group in Eindhoven [15][16][17]. Common factors of these models are the application of a stress dependent viscosity to capture the deformation kinetics and the use of rubber elasticity to model strain hardening.…”
Section: A P = a 2 = (2r-h C )H Cmentioning
confidence: 99%
See 2 more Smart Citations